Multivitamin with L-Arginine Supplementation Can Increase Linear Growth Velocity in Children with Idiopathic Short Stature without Affecting Bone Maturation: L-arginine Supplemantation in Children with Idiopathic Short Stature - Akcagil, Ömer; Ulucan, Korkut; Akçay, Teoman (Progress in Nutrition, 2021)
L-arginine is a well-known growth hormone (GH) stimulator. The aim of the present study was to investigate the effect of L-arginine supplementation on growth velocity in prepubertal boys with idiopathic short stature. In this retrospectively designed study, prepubertal boys over 5 years of age who were diagnosed with idiopathic short stature were randomized into two groups according to their use of multivitamin with arginine (ARGİVİT®) (n=24) or multivitamin without arginine (n=34). Both groups were compared statistically according to growth velocity, IGF-1 and IGF-BP3 SDS and bone age maturation rates before and after 1 year of treatment. Basal IGF-1 SDS and basal IGF-BP3 SDS values ​​of the groups were similar, but after the mean 1-year treatment, IGF-1 and IGFBP3 SDS values ​​of the study group increased significantly compared to the control group. The annual growth velocity of the study group also showed a statistically significant increase compared to the control group. There was no statistical difference between the two groups in terms of bone maturation. L-arginine supplementation can be an inexpensive, safe and effective treatment alternative in idiopathic short stature.